Editorial - Neves, Pedro Soares (CAP - Cadernos de Arte Pública / Public Art Journal, 2021)
Remote interpretation is now digitally distorted. Something considered distant can be equally close, pervasive, a-spatial. With this topic, we intend to open the debate on the tensions caused by the multiple interpretations that the word “remote” in relation with (the complex binomial) “public art”. Is it a remote feeling that will remain? What path did the remote word take to us, today? Is the remote as a medium here to stay? Will the far, off-center (eccentric), have a component of unexpected surprise? What scale is remote, sustainable, green, universal, atomic? With this call for articles, essays, reviews of book or exhibitions, we will seek to draw an overview of the present and the past, crossing views (among many others) from the history of art, sculpture, artistic practices, design, architecture and urbanism.